Teoria do valor e alienação em Marx: uma crítica (nada tradicional) da dominação social no capitalismo - Muniz, Marina Paes Maurício (2024)
The guiding thread of this thesis is the intimate relationship between the category of alienation and Karl Marx's theory of value, which appears for the first time, still incompletely, in the Grundrisse. In order to defend the existence of this intrinsic relationship and its consequences, we have considered Marx's investigations into bourgeois relations of production from the beginning, with the Economic-Philosophical Manuscripts of 1844, to the most developed formulation in Capital (1867), as well as the contributions of other qualified authors. In the first chapter, we analyze the Economic-Philosophical Manuscripts in the light of the theory of value developed in Capital, articulating the notion of generic being present in this work with the ideas present in Gyorgy Lukács' Ontology of Social Being. In the second chapter, we highlight Marx's clarity, in the Grundrisse, that the specificity of capitalism lies in its production process, focusing the critique on value as a historically specific form of wealth and, consequently, on the type of work that creates it. To show that the focus on abstract domination does not contradict the fact that capitalism emerges and expands at the expense of certain peoples and lives, we deal with the historical preconditions for the establishment of this logic, combining critique of value and critique of patriarchy through the contributions of Silvia Federici and Roswitha Scholz. The third chapter explains the connection between alienation and the theory of value, using Marx's Capital and Moishe Postone's reinterpretation, bringing to the center the fundamental categories for understanding our logic of production: commodity, value, abstract labor and capital. We conclude the thesis by arguing that the alienated dynamics of capital effect a specific temporality, constituting a particular form of social domination that is impersonal and abstract, resulting from the alienated dynamics of the capitalist system itself.